2019
DOI: 10.22175/mmb2019.07.0027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Increased Pork Hot Carcass Weights. II: Loin Quality Characteristics and Palatability Ratings

Abstract: The objective of this study was to evaluate the effects of increased pork hot carcass weight on loin quality and palatability of top loin chops. Pork loins (N = 200) were collected from 4 different hot carcass weight groups: A light weight (LT; less than 111.8 kg), medium-light weight (MLT; 111.8 to 119.1 kg), medium-heavy weight (MHVY; 119.1 to 124.4), and a heavyweight group (HVY; 124.4 and greater). Following fabrication, chops were assigned to fat and moisture analysis, Warner-Bratzler shear force (WBSF), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The AMSA sensory guidelines (AMSA, 2015) were followed for the training of sensory panelists. The trained sensory panel training protocol, sample evaluation protocol, scaling, and anchors used were identical to those described by Rice et al (2019). Trained sensory panelists evaluated one sample from each of the programs in a random order within a panel session, for a total of 20 trained panel sessions.…”
Section: Trained Sensory Panelsmentioning
confidence: 99%
“…The AMSA sensory guidelines (AMSA, 2015) were followed for the training of sensory panelists. The trained sensory panel training protocol, sample evaluation protocol, scaling, and anchors used were identical to those described by Rice et al (2019). Trained sensory panelists evaluated one sample from each of the programs in a random order within a panel session, for a total of 20 trained panel sessions.…”
Section: Trained Sensory Panelsmentioning
confidence: 99%
“…Steaks designated for consumer sensory analysis were thawed at 2°C to 4°C for 24 h prior to testing and all exterior fat was removed prior to analysis. Testing followed procedures previously described McKillip et al (2017), Nyquist et al (2018), Rice et al (2019), and Davis et al (2021). Steaks were cooked and prepared for the consumer panelists using the procedures previously described for trained sensory panel evaluation.…”
Section: Consumer Sensory Panel Evaluationmentioning
confidence: 99%
“…Similarly, Rice et al [ 12 ] showed that pork from carcasses weighing more than 125 kg received higher desirable ( p < 0.05) evaluations for appearance and intention to purchase than swine weighing 111 kg. Rice et al [ 13 ] also noted that the juiciness of pork with a slaughter weight of 124 kg was evaluated to be greater ( p < 0.05) than meat from both 119 and 111 kg pig carcasses.…”
Section: Introductionmentioning
confidence: 99%